Skin and Mucosa Care in Systemic Sclerosis – Patients' and Family Caregivers' Experiences and Expectations of a Specific Education Programme: A Qualitative Study. (27th March 2013) - Kocher, Agnes; Adler, Sabine; Spichiger, Elisabeth
Abstract: Background: Skin and mucosal manifestations such as skin thickening, pruritus, reduced microvascular circulation, digital lesions, appearance‐related changes, and dryness of the eyes and mucosa are common in systemic sclerosis (SSc). A specific skin and mucosa care education programme for patients and their family caregivers should increase their self‐efficacy and improve coping strategies. Aims: The aims of this qualitative study were to explore the participants' experiences of both everyday life with skin and mucosal manifestations and the programme itself, while identifying unmet needs for programme development. Methods: Narrative interviews were conducted with eight SSc patients and two family caregivers of individuals with SSc. Using qualitative content analysis techniques, the transcribed interviews were systematically summarized and categories inductively developed. Results: The findings illustrated participants' experiences of skin and mucosal symptoms and revealed them to be experts in finding the right therapy mix alone (before diagnosis) and also in collaboration with health professionals (after diagnosis). Participants emphasized that the programme gave them useful education on skin and mucosa care. They described how they had to cope alone with the lack of information on pathophysiology, people's reactions, and the impact on their family and working lives. Nevertheless, participants said that they maintained a positive attitude by not dwelling on future disabilities. Conclusions: Patients and family caregivers benefited from the individualized and SSc‐specific education on skin and mucosa care. Future improvements to the programme should focus on imparting understandable information on SSc pathophysiology, dealing with disfigurement and seeking reliable disease information, as well as facilitating peer support. Copyright © 2013 John Wiley & Sons, Ltd.